SPECIES COMPOSITION OF FRESHWATER EELS (Anguilla spp.) IN EIGHT RIVERS FLOWING TO PALABUHANRATU BAY, SUKABUMI, INDONESIA - Agus Alim Hakim; M Mukhlis Kamal; Nurlisa A Butet; Ridwan Affandi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Freshwater eel (Anguilla spp.) is a catadromus fish that migrates from freshwater into seawater for spawning and return to freshwater during larvae stage to grow. The objective of this study was to determine species composition of tropical freshwater eels based on morphology collected from several rivers flowing in to the Palabuhan Ratu Bay. Young, adult, and glass eels were caught in August 2014 until Desember 2014. Glass eels were only caught in Cimandiri River. Freshwater eels were classified by ano-dorsal length (AD) divided by total length (TL), cluster analysis, and discriminant analysis based on morphometric data. The results showed different AD/TL of young and adult, i.e., 1.93±0.51 for A. bicolor bicolor, and 16.99±0.65 for A. marmorata, and three different AD/TL of glass eels i.e.,1.72±1.05 for A. bicolor bicolor6.60±1.79 for A. nebulosa nebulosa, and 15.07±1.04 for A. marmorata. Cluster analysis showed three groups of population  characters of young and adult eels i.e.  A. bicolor bicolor (2 groups) and A. marmorata (1 group). Discriminant analysis showed three groups of glass eels population i.e., A. bicolor bicolor, A. nebulosa nebulosa, and A. marmorata. Morphological identification showed that young and adult eels in Cibareno  and Citepus rivers had two species i.e., A. bicolor bicolor and A. marmorata. Glass eels from Cimandiri river had three species i.e., A. bicolorbicolor, A. nebulosanebulosa, and A. marmorata. A. bicolor bicolor was found in each rivers and as a dominant species in Palabuhan Ratu Bay.Keywords: A. bicolor bicolor, A. marmorata, A. nebulosa nebulosa, species composition